DIFFERENT TEST OF ABNORMAL RETURN AND TVA BEFORE AND AFTER STOCK SPLIT ANNOUNCEMENT - Ayu Putri Kukuh Pangesti (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2019)
This study aims to determine whether there are differences in abnormal return (AR) and trading volume activity (TVA) between before and after the announcement of a stock split. The data used in this study are secondary data from the Indonesia Stock Exchange (IDX). Sampling in this study used a purposive sampling method. With certain criteria obtained a sample of 30 companies. This study uses event studies to determine the information content contained in an event. Hypothesis testing conducted in this study uses the normality test and paired sample t-test. The results of testing the first hypothesis in this study indicate that there is no difference in AR between before and after the announcement of a stock split. This happens because investors consider the stock split announcement have no economic value and prefer to allocate their funds to companies that are truly able to provide a return. While in the second hypothesis testing found the same thing that there is no significant TVA difference between before and after the announcement of the stock split.k split.